Hubungan Kepatuhan Diet Dengan Insiden Komplikasi DM Tipe 2: Literature Review - Subagjo, Immaculata Eka; Lumadi, Sih Ageng; Handian, Feriana Ira (Universitas Baiturrahim, 2024)
Diabetes Mellitus (DM) is a health problem that can increase the risk of various complications. Dietary compliance is one of the factors that have an important role in preventing complications in Type 2 DM. This study aims to determine the relationship between dietary compliance with the incidence of complications. The method or design used in this research is Literature Review by searching for journals using databases, namely SCOPUS, Science Direct, PubMed, and Google Scholar which were published between 2014-2021. The analysis in this study is synthesized in a narrative form. All study results show that dietary compliance is associated with complications in patients with Type 2 DM and there is a relationship between dietary adherence and incidence of DM 2. Therefore, the better dietary adherence, the smaller the incidence of Type 2, and vice versa. Suggestions in this study, it is necessary to increase knowledge and attitudes towards dietary compliance to keep blood glucose levels stable and prevent complications